BRAFV600E Immunohistochemistry in Papillary Thyroid Carcinomas: Relationship Between Clinical and Morphological Parameters - UĞURLU, MUSTAFA ÜMİT; ÖZKAN YENAL, NAZİYE (FEDERATION TURKISH PATHOLOGY SOC, 2019)
Objective: To investigate the association of the BRAFV600E mutation with papillary thyroid carcinoma using clinical, morphological and prognostic parameters. We also intend to assess the utility of the BRAFV600E immunohistochemistry and compare it with BRAF polymerase chain reaction (RT-PCR). Material and Method: We applied BRAFV600E immunohistochemistry in a cohort of 107 papillary carcinomas, 19 adenomas and 13 normal thyroid tissues that was chosen retrospectively between 2011 and 2015. Statistical analysis was based on semiquantitative immunohistochemistry findings. We also applied BRAF RT-PCR in a subgroup of 14 papillary carcinomas, 13 metastatic lymph nodes and 4 adenomas that was chosen randomly. Results: In regard to the comparison of BRAFV600E immunohistochemistry and BRAF RT-PCR, a 3+ nuclear and cytoplasmic immunoexpression was considered 'positive The BRAFV600E mutation was most frequently observed in classic variant cases. No mutation was detected in follicular variant cases. The mutational status of the primary tumour and the lymph node metastasis was consistent. A significant relationship of the BRAFV600E mutation was found with prognostic factors such as higher pT stage, classic variant, lymphatic invasion, perineural invasion, lower mitotic index, lack of tumour capsule, intrathyroidal spread and extrathyroidal extension. Conclusion: Immunohistochemistry, using the VE1 clone, is a reliable technique for detection of the BRAFV600E mutation. Our results with immunohistochemistry are consistent with a previous effort. In our study, despite the correlation between some pathological prognostic parameters and the BRAFV600E mutation; poor prognosis was found to be irrelevant overall. Morphological parameters seem to be keener than the BRAFV600E mutation. Nevertheless, different series display different results, possibly due to environmental factors. Considering this and the proven success of targeted therapies against the BRAFV600E mutation a thorough assessment would be important.
Keywords: Thyroid; Papillary carcinoma; BRAFV600E; Immunohistochemistry; Reverse Transcriptase PCR; Prognosis; BRAF V600E MUTATION; LYMPH-NODE METASTASIS; BRAF(V600E) MUTATION; RISK; RECURRENCE; PREDICTOR; TRENDS; IMPACT; TUMORS